Socialization as key process in knowledge management - Francisco José GARCÍA-PEÑALVO (Ediciones Universidad de Salamanca, 2016)
The editorial of this second issue of volume 17,corresponding to 2016, is devoted to socialization process in the knowledge management in order to complement the special section about Social Networks and Education.